2001
DOI: 10.1021/ac001276s
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Gas-Phase Noncovalent Macromolecular Complexes in Electrospray Mass Spectrometry Using Aqueous Triethylammonium Bicarbonate Buffer

Abstract: The use of triethylammonium bicarbonate (TEAB) solution in electrospray mass spectrometry proved to be a very efficient way for studying proteins or noncovalent protein complexes under "nondenaturing" conditions. The low charge states observed in the mass spectra improve the separation of ions arising from macromolecular species of close masses. Moreover, the multiply charged ions generated in a TEAB solution are significantly more stable than those formed under more conventional conditions (for example, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 29 publications
2
77
0
Order By: Relevance
“…Changing the nature of the buffer salt produced little change to the spectra, except that, with everything else being equal, there was a shift towards lower charge states, when triethylammonium bicarbonate was used. This shift is in line with the higher proton affinity of triethylammonia than that of ammonia; the former is expected to be much more efficient than the latter in competing with iNOS for the protons [44]. Furthermore, raising the solution pH from 7 through 10 appeared also to have little effect on the spectra.…”
Section: General Observations For Neutral Inos Solutionsmentioning
confidence: 54%
“…Changing the nature of the buffer salt produced little change to the spectra, except that, with everything else being equal, there was a shift towards lower charge states, when triethylammonium bicarbonate was used. This shift is in line with the higher proton affinity of triethylammonia than that of ammonia; the former is expected to be much more efficient than the latter in competing with iNOS for the protons [44]. Furthermore, raising the solution pH from 7 through 10 appeared also to have little effect on the spectra.…”
Section: General Observations For Neutral Inos Solutionsmentioning
confidence: 54%
“…The solvent for all samples was water. NH 4 AcO and (HNEt 3 )HCO 3 were used to buffer the proteininhibitor solutions; these are well known for conserving noncovalent interactions in ESI [37]. The titration samples contained between 8.8 and 9.0 M AK (depending on the volume of added inhibitor), 0 to 9.6 M P 1 ,P 5 -di(adenosine-5')pentaphosphate (Ap5A) or 0 to 12 M P 1 ,P 4 -di(adenosine-5')tetraphosphate (Ap4A), 50mM (HNEt 3 )HCO 3 , and 500 M EDTA.…”
Section: Methodsmentioning
confidence: 99%
“…The model proposed by de la Mora and Felitsyn also predicts that when other than ammonium acetate buffer salts are used this may influence the charging of globular proteins and protein complexes. It has been shown that triethylammonium bicarbonate can also be used in ESI mass spectrometry for studying intact proteins and non-covalent complexes (Lemaire et al, 2001). In comparison with ammonium bicarbonate or acetate solutions, the use of triethylammonium bicarbonate resulted in significantly less ion charges, which may be explained by the higher gas-phase proton affinity of protonated triethylammonium bicarbonate (Lemaire et al, 2001).…”
Section: Electrospray Ionization Of Biomacromoleculesmentioning
confidence: 99%
“…It has been shown that triethylammonium bicarbonate can also be used in ESI mass spectrometry for studying intact proteins and non-covalent complexes (Lemaire et al, 2001). In comparison with ammonium bicarbonate or acetate solutions, the use of triethylammonium bicarbonate resulted in significantly less ion charges, which may be explained by the higher gas-phase proton affinity of protonated triethylammonium bicarbonate (Lemaire et al, 2001). Moreover, it has been proposed that the multiply charged ions generated in a triethylammonium bicarbonate solution are more stable compared to the traditionally used solutions, making them more suited for the analysis of macromolecular complexes (Lemaire et al, 2001).…”
Section: Electrospray Ionization Of Biomacromoleculesmentioning
confidence: 99%